Detection of Acetamiprid by Aptamer Based on a Porous Silicon Microcavity - Yun Gao (IEEE, 2022)
In this paper, a new method for pesticide detection based on porous silicon microcavities was proposed. First, the aptamer of acetamiprid was fixed in the functionalized porous silicon microcavity. Then, the complementary strand of the aptamer modified with graphene quantum dots was hybridized with the aptamer, and the effective refractive index of the porous silicon microcavity increased. When acetamiprid was added, it bound to the aptamer due to its stronger specificity. The aptamer separated from the complementary strand of the coupled graphene quantum dots and bound to acetamiprid, resulting in a decrease in the effective refractive index, and its central wavelength of reflection spectrum was blue shifted, and the blueshift increased with the increase of acetamiprid concentration. The relationship between the change in central wavelength and the concentration of acetamiprid was analysed, and the detection limit of acetamiprid was 151 nm.